Side Effects in a HEMT Performance with InAlN/GaN - Z. Kourdi; B. Bouazza; A. Guen-Bouazza; M. Khaouani (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
We present a simulation of a HEMT (high electron mobility transistor) structure. We extract the device characteristics through the analysis of DC, AC and high frequency regimes, as shown in this paper. This work demonstrates the optimal device with a gate length of 30 nm, and InAlN/GaN heterostructure for minimizing side effects. The simulated with Silvaco software of the HEMT devices with the materials InAlN show very good scalability in different application. We have demonstrated an excellent current density, as high as 644 mA/mm, a peak extrinsic transconductance of 710 mS/mm at VDS=2 V, and cutting frequency cutoffs of 385 GHZ, maximum frequency of 810 GHz, maximum efficiency of 23% for x-Band, maximum breakdown voltage of 365 V, and an ON/OFF current density ratio higher than 8 x 108. These values were determined through the simulation by hydrodynamics models, which makes that optimize the design is the future of this technology.